First occurrence of musk ox Ovibos moschatus in the Late Pleistocene (MIS 3) record from NW Iberia: Paleobiogeographic and paleoenvironmental implications. (15th June 2020) - Álvarez-Lao, Diego J.; Ballesteros, Daniel; Rivals, Florent; Álvarez-Vena, Adrián; Valenzuela, Pablo; Jiménez-Sánchez, Montserrat
Abstract: A remarkable musk ox ( Ovibos moschatus ) assemblage was recovered at Cowshead Cave (Picos de Europa Mountains, NW Spain). This find is of special paleobiogeographic relevance since it involves the first occurrence of this species in NW Iberia and extends the boundary of its Eurasian distribution range to the SW. Fossils correspond to at least two individuals: one young male about 20 months old, which includes an extraordinarily well-preserved skull, and one subadult of about 38–44 months. The bone deposit, dated to 34.9 ± 0.4 cal ka BP (MIS 3), accumulated in a karst cave that acted as a natural trap, agreeing with the geomorphology and the good preservation of the remains. Considering that musk ox skulls of young individuals are extremely rare in the Pleistocene record, the detailed comparative study of the skull here presented provides new and relevant information. The skull from Cowshead is larger than modern specimens of similar individual age from Greenland; additionally, some remarkable morphological peculiarities in skull and teeth were identified. One metacarpal of the subadult individual was compared to recent and Pleistocene specimens and was among the largest in the entire sample. Significant differences in morphology and size between fossil and recent metacarpals were detected. Teeth microwear analysis suggests a browsing diet based on twigs and leaves at the time of death, which is consistent with a winter diet. The cold and arid environment inferred from the presence of musk ox is consistent with the paleontological record, since cold-adapted mammals occurred at other contemporary assemblages from NW Iberia. Highlights: The first occurrence of Ovibos moschatus fossils at NW Iberia is presented. A new SW border of the Pleistocene O. moschatus Eurasian distribution is established. Remains of two muskox individuals (a young and a subadult) include a complete skull. A comparative study of the fossils provided relevant results on morphology and size. This muskox find indicate cold and arid environment in NW Iberia at 34.9 cal ka BP.